EDUKASI BAHAYA PENGGUNAAN GADGET PADA ANAK SEKOLAH DASAR DI MALUKU TENGAH - Juniler Rumahloine; Elpira Asmin; Muhammad Zaid Wakano; Suay Anabella Wattimena; Dewi Aryanti M. Rusdin; Ritha Tahitu (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
Excessive use of gadgets in children should be avoided so that their development is not disrupted. Visual acuity is the primary indicator of eye health and visual systems. Visual acuity is ability of person to see an object. This public service activity is a form of support for the 2017-2030 Roadmap for Combating Visual Impairment and one of the efforts in preventing visual impairment in children. The activity is a screening of visus examination of 5th and 6th grade elementary school students accompanied by education about the dangers of gadget use in children. The purpose of this vision screening is to determine the visual appearance of refractive errors in elementary school students. The vision screening was using Acuity's PEEK (portable eye examination kit) application. Public service activities were carried out in Waai Village, specifically at SD Negeri 163 Central Maluku, on Friday, October 04, 2024. The were 42 participants who attended the counseling on the dangers of using gadgets, with the results obtained, that is 40 of them with normal vision, and 6 had visual impairment. The implementation of this activity took place in a very effective and efficient manner. This activity is expected to increase the understanding of children and parents regarding the importance of routine eye examinations in children from an early age